Assessing the drivers of india’s agricultural export growth: Scale, competitive and interaction effects - Pires, Averyl; Chandran, B P Sarath (Asian Journal of Agriculture and Rural Development, 2026)
India’s agricultural exports experienced significant growth between 1991 and 2020, and this study analyzes the drivers of that growth using the Constant Market Share (CMS) methodology, which decomposes export performance into scale, competitive, and second-order effects. Most existing CMS studies on India focus on short periods and broad product groups, with limited partner-wise and product-wise detail and little attention to second-order effects. This paper addresses this gap by providing a detailed long-term assessment of India’s agricultural export performance. The results show that the scale effect is the principal driver of export growth, accounting for nearly 60 percent of the total increase, largely reflecting favorable international market conditions. Competitive effects vary across product categories, with market share gains in meat, cereals, and tobacco, while sugar, beverages, and vegetable plaiting materials experienced declining competitiveness. The second-order effect, which captures interactions between structural demand shifts and competitiveness, shows a mixed pattern and offsets nearly 20–30 percent of potential gains in several cases, indicating India's limited ability to consistently exploit favorable global demand. Products such as edible fruits and beverages illustrate this mismatch, whereas exports of live animals and sugar benefited from stronger structural alignment. The findings highlight important policy implications, emphasizing product diversification, quality upgrading, improved logistics, and stronger market intelligence to enhance agricultural export competitiveness.